Mangrove soil as a natural catalyst for green synthesis of silver nanoparticles - Chacón-Calderón, Andrea; Zuñiga-Umaña, Juan Miguel; Villarreal, Claudia; Vega-Baudrit, José Roberto; Pereira-Reyes, Reinaldo; Corrales-Ureña, Yendry Regina (Frontiers in Chemistry, 2025)
IntroductionMangrove ecosystems host diverse biogeochemical pathways that enhance their resilience against a wide range of pollutants, from heavy metals to hormones. The unique combination of extreme physicochemical soil conditions and the anaerobic metabolism of mangrove microbiota creates favorable conditions for nanoscale processes.MethodsThe presence of naturally occurring nanoparticles in soil extracts from Costa Rican mangroves at Punta Morales and Cahuita was characterized. Furthermore, we evaluated the ability of these soil extracts to catalyze the formation of silver nanoparticles (AgNPs) under sunlight in saline environments (28°C–31°C within 15 min). Characterization techniques such as transmission electron microscopy (TEM) with selected area electron diffraction (SAED), energy-dispersive X-ray spectroscopy (EDS), Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and UV–Vis spectrophotomery (UV-vis) were used. To investigate the reaction mechanism, we quantified reactive oxygen species (ROS) generated under sunlight and UV light, monitored changes in the absorption bands of the extracts, conducted nanoparticle synthesis in the dark, and measured the reduction potential of the extracts. Ag NPs–extract interactions were evaluated using isothermal titration calorimetry (ITC), and antimicrobial activity was assessed via minimum inhibitory concentration (MIC) assays against Escherichia coli (E. coli), Staphylococcus aureus (S. aureus), and Bacillus subtilis (B. subtilis). Bacterial growth was analyzed using generalized additive models (GAM) and non-parametric tests at specific time points.ResultsMangrove sediments contained nanoparticles, primarily silicates and carbon-based organic fibers. Soil extracts catalyzed nanoparticle formation, producing mainly Ag NPs and AgCl particles. Pacific extracts showed a higher affinity for the Ag NPs, while Caribbean extracts enabled faster AgNP synthesis due to a higher density of organic binding sites. The proposed mechanism involves organic matter reduction of silver, photolysis, and catalytic ion effects (e.g., iron). Antimicrobial tests revealed species-specific and concentration-dependent responses, with MIC values between 2.5 and 20 μg/mL, depending on bacterial strain and nanoparticle origin. AgNPs synthesized with Caribbean extracts exhibited stronger antimicrobial activity compared to those synthesized with citric acid, highlighting the potential role of humic and fulvic acid coatings.DiscussionOur findings suggest that mangrove soils naturally harbor nanoscale materials and act as efficient biogenic catalysts for metallic nanoparticle synthesis. The distinct properties of extracts from different mangrove regions influence both the synthesis kinetics and the biological activity of the nanoparticles. This underscores the ecological and biotechnological relevance of mangrove-derived materials.